Akses Media Baru Oleh Remaja SMA Kota Semarang dan Hubungannya Dengan Interaksi Dengan Lingkungan Sekitar Pada Siswa Kelas X SMA 5 Kota Semarang - Norhabiba, Fitri (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractCharacteristic of new media create ilution as face to face communication. Internet uses morehigher have decrease communication in real world, such as with family, increase depression andloneliness. Internet remove social relationship by face to face.This research try to test uses and gratification aspect and computer mediated communicationini correlation with benefit of student media access. Sampel research is student of class X SMA 5Semarang, 36 students have selected by systematic random sampling.It concluded that more higher internet access did not affect on intensity of family interactionand friends. Person correlation showed that there’s positive correlation, strong, and significantr(36)=0,447 and 0,541, p<0,01. More higher internet acces, more higher too frequent of interactionwith family and friends.